Adipose-androgen crosstalk in polycystic ovary syndrome: mechanisms and therapeutic implications - Ni, Muchu; Lei, Hongyan; Ye, Tao; Wang, Yongzhou (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) is the most common endocrine-metabolic disorder in reproductive-age women, characterized by hyperandrogenism (HA) and insulin resistance (IR). Despite its high prevalence, the underlying pathophysiology remains incompletely understood. In recent years, bidirectional interactions between androgens and adipose tissue (AT) have been recognized as a key driver of the vicious cycle in PCOS. This review systematically examines this core interaction mechanism: on one hand, dysfunctional AT (particularly visceral fat) exacerbates ovarian androgen overproduction by intensifying IR, inducing chronic low-grade inflammation (e.g., elevated TNF-α and IL-6), and reducing adiponectin levels. Conversely, HÀ exacerbates AT dysfunction and systemic IR by altering body fat distribution (central obesity), suppressing lipogenesis, impairing lipolysis, and disrupting adipokine secretion (e.g., reduced adiponectin, elevated leptin). This bidirectional positive feedback loop within the fat-androgen axis perpetuates the worsening metabolic and reproductive abnormalities in PCOS. Based on this mechanism, existing therapeutic strategies—including lifestyle interventions, insulin sensitizers (e.g., metformin), GLP-1 receptor agonists, and anti-androgens—partially exert their effects by improving AT function and antagonizing androgenic effects. Emerging therapies such as SGLT-2 inhibitors, BAT transplantation, anti-TNF-α therapies, and gut microbiota targeting offer promising new avenues for directly intervening in this axis and breaking the vicious cycle of PCOS. A deeper understanding of fat-androgen interactions is crucial for developing precision treatments for PCOS.